Optical Cable Backbone Network Design in West Kalimantan Province Using OTN DWDM Technology - Azarya NJ Siahaan; Saut Situmorang; Charla Tri Selda Manik (Journal of Science Technology (JoSTec), 2020)
In designing the backbone network for the province of West Kalimantan using Dense Wavelength Division Multiplexing (DWDM) and Optical Transport Network (OTN) devices which cover 14 districts and cities consisting of 30 segments, of which 30 segments consist of 14 DWDM OTN sites and 8 Optical Land Amplifier sites ( OLA). From the results of the design and simulation of the backbone network, it was found that the value of the Optical Link Power Budget (OLPB) < 50 dBm where this value is the ideal value in deploying a DWDM OTN backbone network, and the range of the Optical Signal Noise Ratio (OSNR) is between 20 dBm < OSNR < 40 dBm, which is the ideal value for OSNR, and has an Optical Rise Time Budget (ORTB) < 60 ps, and also has a segment margin system of > 7 dB.